Production and Role of Hormones During Interaction of Fusarium Species With Maize (Zea mays L.) Seedlings - Vrabka, Josef; Niehaus, Eva-Maria; Münsterkötter, Martin; Proctor, Robert H.; Brown, Daren W.; Novák, Ondřej; Pěnčik, Aleš; Tarkowská, Danuše; Hromadová, Kristýna; Hradilová, Michaela; Oklešt’ková, Jana; Oren-Young, Liat; et al. (Frontiers in Plant Science, 2019)
It has long been known that hormones affect the interaction of a phytopathogen with its host plant. The pathogen can cause changes in plant hormone homeostasis directly by affecting biosynthesis or metabolism in the plant or by synthesizing and secreting the hormone itself. We previously demonstrated that pathogenic fungi of the Fusarium species complex are able to produce three major types of hormones: auxins, cytokinins and gibberellins. In this work, we explore changes in the levels of the three aforementioned hormones in infected maize and mango plant tissues. The ability to produce individual phytohormones varies significantly across Fusarium species and such differences likely impact host specificity and induce unique responses in planta during infection. For example, the production of gibberellins by F. fujikuroi leads to the suppression of gibberellin biosynthesis in plant tissue. We also found that although all Fusarium species are able to synthesize auxin, sometimes by multiple pathways, the ratio of its free form and conjugates in infected tissue is affected more than the total amount produced. The recently characterized unique pathway for cytokinin de novo synthesis in Fusarium appears silenced or non-functional in all studied species during plant infection. Despite this, a huge increase in cytokinin levels was detected in F. mangiferae infected plants, caused by the up-regulation of plant genes responsible for their biosynthesis. Thus, the accumulation of active cytokinins may contribute to mango malformation of the reproductive organs upon infection of mango trees. Together, our findings provide insight into the complex role fungal and plant derived hormones play in the fungal-plant interactions.